1998
DOI: 10.1046/j.1365-2249.1998.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of inducible nitric oxide synthase and transforming growth factor-beta (TGF-β) in leprosy lesions

Abstract: SUMMARYInducible nitric oxide synthase (iNOS) and TGF-b were localized by immunocytochemistry in skin lesions from patients across the leprosy spectrum, and from patients undergoing reversal reaction. iNOS expression was highest at the tuberculoid pole of the spectrum, and increased during reversal reaction. TGF-b was observed throughout the leprosy spectrum, but was highest at the lepromatous pole. Levels of TGF-b decreased during reversal reaction. Reduced levels of TGF-b may contribute to unregulated inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
21
1
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 18 publications
9
21
1
6
Order By: Relevance
“…However, several studies have shown that iNOS is expressed, as detected by immunohistochemistry, at the site of disease in patients infected with intracellular pathogens, including M. leprae. Khanolkar-Young et al (210), using antibodies against iNOS, found that iNOS was highly expressed in the lesions of tuberculoid leprosy patients and was increased to even higher levels during the reversal reaction (see below). Moreover, the levels of iNOS subsided over the course of prednisolone treatment (233).…”
Section: (Iii) Cytotoxic Cells (A) T Cells Cd8mentioning
confidence: 99%
“…However, several studies have shown that iNOS is expressed, as detected by immunohistochemistry, at the site of disease in patients infected with intracellular pathogens, including M. leprae. Khanolkar-Young et al (210), using antibodies against iNOS, found that iNOS was highly expressed in the lesions of tuberculoid leprosy patients and was increased to even higher levels during the reversal reaction (see below). Moreover, the levels of iNOS subsided over the course of prednisolone treatment (233).…”
Section: (Iii) Cytotoxic Cells (A) T Cells Cd8mentioning
confidence: 99%
“…Hence, down-regulation of TNF-␣ could be crucial for reducing inflammation during reactions. Expression of tumor necrosis factor ␤1 (TGF-␤1), an important regulator of inflammation and wound healing, is decreased in skin in T1R (18), and thus up-regulation of TGF-␤1 could be beneficial for resolution of the reaction.…”
mentioning
confidence: 99%
“…There is an influx of CD4 ϩ cells into lesions (10), and elevated levels of cytokine mRNA and protein have been detected in situ, including IFN-␥, IL-1␤, IL-2, IL-12, and tumor necrosis factor ␣ (4, 7, 14-16). Furthermore, increased levels of the enzymeinducible nitric oxide synthase (iNOS) are found in reactional lesions (8), indicating an enhanced intracellular killing capacity of macrophages. Reactions are painful and frequently result in significant nerve damage.…”
mentioning
confidence: 99%